The advertisement call and clutch size of the Golden-capped Boulder-frog Cophixalus pakayakulangun (Anura: Microhylidae) - Aland, Kieran V.; Hoskin, Conrad J. (Zootaxa, 2013)
In Australia, the family Microhylidae consists of 19 species of Cophixalus Boettger 1892 and 5 species of Austrochaperina Fry 1912 (Hoskin 2012; Hoskin, submitted). Most of these species have highly localized distributions in the rainforests and boulder-fields of north-east Australia (Zweifel 1985; Hoskin 2004; Hoskin & Aland 2011). Australian microhylid frogs are terrestrial breeders with direct development (Zweifel 1985; Hoskin 2004; Anstis et al. 2011). The natural history of Australia’s microhylids is fairly well known, with the basics of breeding biology such as calls and clutch sizes published for most species (Zweifel 1985; Hoskin 2004; Anstis et al. 2011; Hoskin & Aland 2011; Hoskin 2012; Hoskin, submitted). Hoskin & Aland (2011) described two new species from Cape York Peninsula, C. pakayakulangun and C. kulakula, each restricted to boulder-field areas only 30 km apart but readily distinguished by morphology and genetics. Calls could not be compared because the call of C. pakayakulangun was not known at that time. Clutch information for C. pakayakulangun was also not available at the time of description.